Experiences in the Use of the Internet at Egerton University Library, Njoro-Kenya - Nyamboga, Constantine Matoke; Ongondo, Millicent A.; Ongus, Raymond Wafula (DESIDOC Journal of Library & Information Technology, 2003)
University libraries have long desired one–stop shopping for their clienteles and, in this period of electronic age, their clienteles are demanding for it. They need to search from a single point at any physical location, and retrieve information from citations in journal indexes, abstracts and full text information from the electronic sources. This paper reports findings of a study undertaken in late 2003, which aimed to identify how far the use of internet has enhanced teaching, research and scholarly communication at Egerton University. The study involved students, faculty members and library staff. Apart from fairly maintained internet services, the results of this study show that use, interest and confidence in using the internet by female respondents is less compared to male respondents. E-mail and search engines were found to be the most frequently used resources and tools of internet. It also explored that majority of both the library staff and users have not received any instructions in the use of internet. Besides, charges for internet within the university libraries and other university service points are exorbitant and somewhat prohibitive. http://dx.doi.org/10.14429/dbit.24.5.3635